Creating Self-Therapist spaces in the architecture of the interior surfaces of hospitals by modeling the methods used in traditional Iranian mosques - Vahid Parhoodeh; Farah Habib (Fasa University of Medical Sciences, 2020)
The impact of architectural space and its colors on patients is one of the fundamental principles and important challenges in the construction of hospitals. In addition to the practical and physical aspects of the effectiveness of the patient's treatment, this effect is one of great importance to the mental and psychological aspects left over from the treatment period. The depth of this effect is more noticeable in the patient's living space - that is, in the area where he spends more time - and in the mood and vivacity of the treatment staff, who may spend more than half of their life in this space. They have a dramatic impact. The use of inspiring elements is not specific to the architecture of medical centers but is even used in the architecture of other buildings, such as ordinary houses. The peak of the use of these elements can be found in the architecture of places of worship, shrines, and especially in traditional Iranian mosques. In this research, these therapeutic elements are first introduced in the architectural structure, especially the architecture of the interior surfaces of traditional Iranian mosques, and then how they are used to create space and design the interior of hospitals. Based on the studies, the combination of architecture used in the interior of Iranian mosques with the architectural design requirements of a medical space can effectively promote the mood, vitality, and mental health of patients and medical staff.